2012
DOI: 10.1140/epja/i2012-12102-x
|View full text |Cite
|
Sign up to set email alerts
|

Quasi-elastic backscattering of 6,7Li on light, medium and heavy targets at near- and sub-barrier energies

Abstract: Abstract.We have performed precision elastic backscattering measurements for the weakly bound nuclei 6,7 Li on the medium and heavy mass targets 58 Ni, 116,120 Sn and 208 Pb at sub-and near-barrier energies (E c.m./Vbar = 0.6 to 1.3). Excitation functions of elastic scattering cross-sections have been measured at ±160• and ±170• and the corresponding ratios to Rutherford scattering and relevant barrier distributions have been extracted. These measurements complement recent work on a 28 Si target, for probing s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
26
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 46 publications
3
26
0
Order By: Relevance
“…For comparison, in Fig. 6 we present an excitation function for the elastic scattering of 6 Li + 120 Sn from earlier measurements [28]. The data correspond to an angular range of 160 o ≤ θ Lab ≤ 170 o .…”
Section: Standard Optical Model Calculationsmentioning
confidence: 94%
See 2 more Smart Citations
“…For comparison, in Fig. 6 we present an excitation function for the elastic scattering of 6 Li + 120 Sn from earlier measurements [28]. The data correspond to an angular range of 160 o ≤ θ Lab ≤ 170 o .…”
Section: Standard Optical Model Calculationsmentioning
confidence: 94%
“…In addition to our data, other experimental elastic scattering cross sections, for systems involving 120 Sn as target, were obtained from [22][23][24][25][26][27][28][29].…”
Section: The Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Owing to conservation of the reaction flux, the fusion and QEL scattering process can be considered complementary and barrier distributions obtained from both types of measurements are expected to be similar [8]. Recently such studies have been carried out using weakly bound stable nuclei [9][10][11][12][13][14][15]. In some cases [9,10,13] it has been found that the barrier distribution obtained from QEL scattering including only the elastic + inelastic + transfer channels peaks at a lower energy compared to the corresponding barrier distribution obtained from fusion.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies of fusion barrier distributions for systems with weakly bound projectiles have been reported about a decade ago [16][17][18][19]. QEL and elastic-scattering barrier distributions for systems involving weakly bound nuclei have been studied only recently [12,[20][21][22][23][24][25][26], with the exception of Ref. [17].…”
Section: Introductionmentioning
confidence: 99%